Impact of cryoballoon applications on lesion gaps detected by magnetic resonance after pulmonary vein isolation. (30th January 2020) - Trotta, Omar; Alarcón, Francisco; Guasch, Eduard; Benito, Eva Maria; San Antonio, Rodolfo; Perea, Rosario J.; Prat‐Gonzalez, Susanna; Apolo, Jose; Sitges, Marta; Tolosana, José María; Mont, Lluís; ,
Abstract: Introduction: Ablation with second‐generation cryoballoon technology evolves as an effective and safe alternative to radiofrequency for atrial fibrillation ablation procedures. Nevertheless, the optimal freezing strategy remains unknown. Our objective was to identify the procedural cryoablation parameters predicting successful peri‐pulmonary vein (PV) lesions by directly analyzing Postablation gaps in late‐gadolinium‐enhanced cardiac magnetic resonance (LGE‐CMR). Methods and Results: Forty‐nine consecutive patients (196 PVs) undergoing ablation with second‐generation cryoballoon at our center were included. The number and duration of cryoballoon application to achieve PV isolation were left to operator discretion. Gap number and length were quantified in all patients with a LGE‐CMR performed 3 months postablation. Application time (420 ± 217 seconds), number of applications (2.1 ± 1.2), application time after electrical isolation (311 ± 194 seconds) and minimum temperature (−45.8 ± 6.5°C) were similar in the 4 PVs. Gaps were observed in 148 PVs (76%), averaging 1.3 ± 1 gaps per vein. Gaps were longer and more frequent in the right PVs (91% vs 59% in left PVs, P < .001). Neither the number, total duration of applications, nor postisolation application time predicted relative length or number of gaps. Conclusions: After successful PV isolation was achieved in patients undergoing cryoablation, increasing the number of applications, the total application time or application time postisolation did not result in a reduction in the number or the relative length of gaps.